Children's comprehension of two types of syntactic ambiguity. Issue 1 (February 2017) - Zimmer, Elly Jane
This study asks whether children accept both interpretations of ambiguous sentences with contexts supporting each option. Twenty-six 3- to 5-year-old English-speaking children and a control group of 30 English-speaking adults participated in a truth value judgment task. As a step towards evaluating the complexity of syntactic ambiguity, the materials included prepositional phrase ambiguities (e.g., The boy saw the girl with binoculars.) and reduced relative clause ambiguities (e.g., The boy saw the girl using a magnifying glass.). Children generally accepted both interpretations of such ambiguities. This suggests that children this age have not only mastered the syntactic configurations associated with these ambiguities, but they can appropriately assign multiple possible structural analyses to an individual expression. Children did reject more interpretations than adults. This may be due to differences in the developing parser and the adult parser.